Does social media use on smartphones influence endurance, power, and swimming performance in high-level swimmers? - Fortes, L. S.; Nakamura, F. Y.; Lima-Junior, D.; Ferreira, M. E.; Fonseca, F. S. (Research Quarterly for Exercise and Sport, 2022)
Objective: This study aimed to investigate the repeated effect of social media on smartphones immediately before training sessions on inhibitory control (Stroop task), endurance (tethered swimming), countermovement jump (CMJ), and swimming performance (50, 100, and 400-m freestyle) in high-level female swimmers.